SYNTHESIS AND ANTIBACTERIAL EVALUATION OF NEW PYRROLO[3’,4’:3,4]PYRROLO[1,2-a]QUINOLINE AND PYRROLO[3’,4’:3,4]PYRROLO[2,1-a]ISOQUINOLINE DERIVATIVES - MATARNEH, Cristina M. AL; SARDARU, Monica C.; APOSTU, Mircea O.; ROSCA, Irina; CIOBANU, Catalina I.; MANGALAGIU, Ionel I.; DANAC, Ramona (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Two series of new fused pyrrolo[3’,4’:3,4]pyrrolo[1,2-a]quinoline and pyrrolo[3',4':3,4]pyrrolo[2,1-a]isoquinoline derivatives were synthesized and evaluated for the antimicrobial activity. The synthetic approach involves cycloimmonium ylides as 1,3-dipol intermediates. The structures of all synthesized compounds were proved by analytical and spectroscopic data. Crystal structure of compound 11a has been also determined by single crystal XRD. The synthesized compounds were evaluated for their expected antimicrobial activity against Staphylococcus aureus ATCC25923, Escherichia coli ATCC25922 and Candida albicans ATCC10231, but no one showed activity against all the reference strains.